ePIC 2025 Keynote: Unpacking individual rights to recognition in the Global Convention on Higher Education (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
The Global Convention on Higher Education is the first international treaty to establish universal principles for fair, transparent, and non-discriminatory recognition of qualifications and achieved learning outcomes. With over seven million students studying abroad and the rapid rise of transnational education, quality assurance and recognition increasingly affect diverse learners beyond higher education, especially those without access to quality learning opportunities. This session examined how the Global Convention frames individual rights to have learning assessed and recognized and highlights flexible approaches to recognition as well as persistent gaps globally. The discussion provided opportunities for participants to reflect on human rights and the future of lifelong learning systems, considering how the Global Convention can renew and reshape commitments to Education 2030. Keywords: human rights, SDG4, lifelong learning, Global Convention on Higher Education, UNESCO